Pengembangan Media Pembelajaran Matematika Berbasis IoT dengan Pendekatan Problem Based Learning - Itqan, Moh. Syadidul; Arrahmani, Novi Ida Fitriyah (Indonesian Journal Publisher, 2024)
This research aims to develop an Internet of Things (IoT)-based mathematics learning medium using a Problem-Based Learning (PBL) approach and evaluate its effectiveness in enhancing students' problem-solving skills. The research method employed is Research and Development (R&D), consisting of stages such as needs analysis, media design, prototype development, field trial, and evaluation. The research subjects consist of 11th-grade students at MAN 1 Probolinggo. The IoT-based mathematics learning medium is designed to facilitate dynamic interaction between students and real-world objects through IoT connectivity. This medium allows students to experience direct learning and actively participate in solving mathematical problems in real-life contexts. The results of this research anticipate that the use of IoT-based learning media with a PBL approach significantly improves problem-solving skills compared to conventional learning methods. Furthermore, it is expected that positive responses from students and teachers to this medium can be integrated into existing mathematics curricula. Therefore, the development of IoT-based mathematics learning media with a PBL approach is expected to be an effective alternative in enhancing students' mathematical problem-solving skills. This medium enables students to actively engage in learning, fosters creativity, and connects mathematical concepts with the real world. Additionally, the results of this research are expected to make a positive contribution to the development of innovative and technology-relevant mathematics teaching methods.